Improve Carrier Generation and Collection with a Nanotube Photovoltaic Configuration (Journal of Advances and Scholarly Researches in Allied Education, 2023)
By using an anodic aluminum oxide membrane, we were able to manufacture semiconductornanotubes with tunable geometric features on a transparent substrate. Three-dimensional nanotubesolar cells are produced with semiconductor absorbers loaded not only in the nanotubes' inner core butalso in the innertube space between the nanotubes, thereby eliminating the need for a membrane.Carriers are created and separated in the nanotube solar cells in three different locations the nanotubecore, the intertube space between nanotubes along the radial direction, and above the nanotubes alongthe axial direction. To prove the efficacy of this strategy, nanotube CdS-CdTe solar cells were producedin early tests. There is a robust and broad-spectrum response of quantum efficiency in nanotube CdSCdTesolar cells, showing increased light absorption and carrier production and collection. Despite nothaving an antireflection coating, the cells showed a high-power conversion efficiency of 10.7 under1Sun illumination and a broad-spectrum response of quantum efficiency (short current density of 25.5mAcm2 open circuit voltage of 750 mV luminous intensity of 750 nm). Materials and electro-opticalcharacterizations showed that the junction and interface behavior of these 3D nanotube solar cells waswell characterized.